Odpowiedzi

2009-09-29T20:16:45+02:00
2009-09-29T20:18:15+02:00
G)23,5*10 do potegi -11=2,35*10do pot-12=0,235 *10 do pot -13

lub inaczej23,5*10 do potegi -11=235*10 do pot -10
h)0,8*10 do potegi-5 =0.08 *10 do pot -6
lub 0,8 *10do pot -5=8 * 10 do pot -4
2009-09-29T22:42:36+02:00
G) 23,5 * 10 do potęgi -11 = 2,35 * 10 do potęgi -12 = 0,235 * 10 do potęgi -13
bądź inaczej 23,5 * 10 do potęgi -11 = 235 * 10 do potęgi -10

h) 0,8 * 10 do potęgi -5 = 0,08 * 10 do potęgi -6
bądź 0,8 * 10 do potęgi -5 = 8 * 10 do potęgi -4